The Role of the Education Office in Fostering Child-Friendly Schools - Aisyah Rahmatul Jannah; Ni'matus Sholihah; Mukhlishah AM (Jawda: Journal of Islamic Education Management, 2026)
This study aims to analyze the role of the Sidoarjo Regency Education Office in fostering the implementation of Child-Friendly Schools (CFS). This research employed a qualitative descriptive approach, with data collected through in-depth interviews, observations, and documentation studies. The findings indicate that the Education Office plays a strategic role through preventive guidance, continuous socialization, responsive complaint-handling mechanisms with a maximum three-day response time, the establishment of School Violence Prevention and Handling Teams (TPPK), and cross-sector collaboration. These strategies demonstrate that the role of the Education Office extends beyond administrative functions to include governance and child protection responsibilities within the education system. This study contributes to the development of educational governance studies by highlighting the importance of local government involvement in strengthening child protection policies in schools.